SOCIO-DEMOGRAPHIC DETERMINANTS OF CREDIT RATIONING AT BAITUL MAAL WA TAMWIL IN INDONESIA - Permata Wulandari; Salina Kassim (Bank Indonesia, 2019)
This study seeks to identify credit rationing socio-demographic determinants to Islamic microfinance to achieve welfare improving goals in three Bottom of the Economic Pyramid (BOP) regions: Yogyakarta, East Lombok and Makassar, South Sulawesi, Indonesia. Another primary focus of this study is to highlight the suggested solutions from Islamic microfinance practitioners to overcome the challenges in the practice of credit rationing assessment. 2,650 borrowers at the BOP in 26 Islamic Microfinance Institutions (MFIs) in Indonesia were selected based on cluster sampling and purposive sampling methods. A questionnaire is adapted from several previous studies. Multinomial logistics regression is used in this paper. Results show that the determinant of credit rationing based on socio-demographic factors, reflecting certain socio-demographic factors that include age, gender, account balance, dependents, salary, monthly income, formal education, access to financing facility in the previous year, distance, and years of saving, has significant influence on the probability of getting financing. Thus, in order to reduce the credit-rationing problem, the major implications from this study are that Baitul Maal wa Tamwil (BMT) should enhance the participation of women, using monthly income rather than salary determinants, provide credit plus financing and realize a one village one BMT program. The solutionswould enhance the participation of BOP borrowers at BMT.